2015
DOI: 10.15403/jgld.2014.1121.fly
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii for the Prevention of Hospital Onset Clostridium difficile Infection

Abstract: Removal of S. boulardii administration to patients receiving broad spectrum antibiotics and the hospital formulary did not impact the rate of hospital onset C. difficile infection in either the hospital population or patients receiving broad spectrum antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…24,25 In contrast, an observational study reported no difference in CDI (9.9 of 10,000 patient days vs 10.4 of 10,000 patient-days) after cessation of twice daily 250 mg dosing of Saccharomyces boulardii with antibiotics without changing other C. difficile preventive measures. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In contrast, an observational study reported no difference in CDI (9.9 of 10,000 patient days vs 10.4 of 10,000 patient-days) after cessation of twice daily 250 mg dosing of Saccharomyces boulardii with antibiotics without changing other C. difficile preventive measures. 26 …”
Section: Resultsmentioning
confidence: 99%
“…In the only CHG study that showed a reduction in CDI in acute care hospitals, Rupp et al, 26 speculated that scrubbing in addition to bed bathing might reduce the overall presence of spores.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting results have also been reported by Lim et al (2015) , suggesting that yeasts can enhance the growth of other probiotics under acidic conditions: Saccharomyces cerevisiae EC-1118 was found to significantly enhance the viability of the probiotic strain Lactobacillus rhamnosus HN001 at pH 2.5–4.0. The use of S. boulardii in reduction of C. difficile infection relapse is still under debate due to controversial results of clinical trials ( Flatley et al, 2015 ). Among other yeasts species, Torulaspora delbrueckii, Debaromyces hansenii, Yarrowia lipolytica, Kluyveromyces lactis, Kluyveromyces marxianus, and Kluyveromyces lodderae have shown strong antagonistic effect against pathogenic bacteria and high acid tolerance ( Kumura et al, 2004 ; Psani and Kotzekidou, 2006 ; Chen et al, 2010 ).…”
Section: Probiotic Bacteriamentioning
confidence: 99%
“…S. boulardii has been extensively studied for its probiotic effects against gastrointestinal tract disorders (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The clinical activities of S. boulardii relevant to antibiotic-associated diarrhea and recurrent Clostridium difficile intestinal infections have been reported (8,(15)(16)(17)(18). S. boulardii is also called S. cerevisiae var.…”
mentioning
confidence: 99%